Energy Tax Incentives in the 108th Congress : A Comparison of the House and Senate Versions of H.R. 6 and the Senate Finance Committee Amendment. (U.S. Congressional Research., 2003)
Compares House and Senate versions of H.R. 6 and Senate amendment to H.R. 6 that is almost identical to S. 1149, all to establish measures to provide incentives to increase the supply of and reduce the demand for fossil fuels and electricity. Explains provisions to promote energy efficiency and use of renewable and alternative fuels in the business, residential, and transportation sectors, reviews miscellaneous tax and non-tax provisions, and delineates revenue offsets.